Pengaruh Viral marketing Dan Word Of Mouth Terhadap Brand Image Aisan games 2018 - Hatta, Muhammad (Equator Journal of Management and Entrepreneurship (EJME), 2020)
This study aims to analyze the influence of Viral Marketing and Word Of Mouth on the 2018 Asian Games Brand Image in Palembang City. This type of research is casual comparative research, which describes the causal effect between research variables. Primary data sources were collected by distributing questionnaires. The sample used in this study were 100 student respondents at Sriwijaya University, Palembang City. The sample in this study was taken using the simple random sampling method and then processed using the help of Statistics for Product and Service Solution (SPSS) version 26. The results obtained indicate that there is a significant influence between Viral Marketing and Word of Mouth on Brand. Picture.